An observational study of aetiology of preterm labour in a tertiary health care centre - Shaheen, Arshi; Chauhan, Nidhi; Alka, Alka; Nautiyal, Ruchira (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Preterm labor and delivery are very challenging obstetric complications encountered by obstetrician as preterm births are the major cause of perinatal and neonatal morbidity and mortality. Methods: An observational study was conducted in the Department of Obstetrics and Gynaecology, Himalayan Institute of Medical Sciences (HIMS), Jollygrant, Dehradun, over a period of one year in which 105 preterm pregnant were observed and risk factors associated with preterm labour were evaluated. Results: Preterm labour was more common in multigravida as compared to primigravida. Maximum (58.10%) number of preterm birth occurred after 32 weeks of gestation. In previous history of pregnancy most important history was previous history of abortion than previous history of preterm labour. Previous one history of abortion was more commonly associated than previous history of 2 or more than 2 abortions. Preterm prelabour rupture of membranes was most important risk factor associated with preterm labour and delivery followed by UTI, than PIH and anemia being the 4th important reason. Conclusions: Thus we concluded that various risk factors that lead to preterm labor are identifiable and mostly are modifiable. Therefore, preconceptional counseling has a great role to play in bringing down the incidence of preterm labour.